Design of a general complex problem-solving architecture based on task management and predictive optimization. (June 2022) - Ahmad, Shabir; Khan, Salman; Jamil, Faisal; Qayyum, Faiza; Ali, Abid; Kim, DoHyeun
Many real-life problems have different contradicting goals and no simple solution. Therefore, an analysis is made to select the appropriate solution based on the scenario, which is considered the best compromise toward the achievement of a goal. In literature, it is known as complex problem-solving and is a kind of paradigm that has been around since the last century, but the cognition involved in complex problem-solving has purely relied on experts in the field. However, with the evolution of the current stack of technologies such as artificial intelligence and the Internet of Things, it is quite possible to perform the cognition process with the help of machines based on the previously-trained historical data. Our previous work proposed the complex problem-solving as a service for smart cities. In this article, we extend this work and propose a generic architecture for complex problem-solving using task orchestration and predictive optimization in Internet of Things–enabled generic smart space. The proposed framework makes use of historical data for artificial cognition of the complexity of the given problem. For this, predictive optimization is used, which identifies the problem and intelligently predict the solution based on the given constraints. The task orchestration architecture is used to decompose the complex problem into small tasks for real-world deployment into sensors and actuators. The architecture is evaluated against different load conditions and different categories of problems, and the results suggest that the proposed architecture can be used a commonplace for different smart space solutions.